The Role of Information Systems in the Effectiveness of Supply Chain Management - Yuyus Yudistria (Journal of Management Practices, Humanities and Social Sciences, 2019)
The purpose of this paper is to analyze the conceptual role of Information System (IS) in the effectiveness of Supply Chain Management (SCM). The development of business competition in the field of products or services is increasingly competitive. Competition for product quality is intense in the market. Since products and services are the fastest growing industries in 2018, so it is very necessary to have a good and structured IS that serves to increase the effectiveness of SCM; this will eventually have a positive impact on business performance. At present the IS is needed to increase the effectiveness of SCM. SCM information systems can standardize, monitor, capture and utilize business potential in order to improve business performance. This study adopted a conceptual approach from related theories. To obtain data, interviews of experts/operational management experts (IS & SCM) were conducted with prompts or probing methods. Moreover, secondary sources such as journals, books and magazines were also used to obtain data. The findings of the study assured the significant role of management IS in achieving effectiveness in SCM. This study concludes that the application of information systems can reduce costs in distribution both from upstream to downstream, can implement good communication and can improve the performance of a company in carrying out SCM.